PERLINDUNGAN KONSUMEN TERKAIT PEREDARAN PRODUK IMPOR TANPA LABEL HALAL DI INDONESIA - Wiwik Afidah; Anang Dony Irawan (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Along with the globalization of trade that leads to a free market, resulting in more and more variations of products being sold, both in the form of products and services. This, on the other hand, has benefits for consumers, but on the other hand, it has the potential to harm consumers due to the actions of business actors in producing goods and services often not paying attention to consumer rights related to existing legal provisions, in this case the inclusion of labels. Halal for imported products Law Number 8 of 1999 and Government Regulation No. 69 of 1999 as a legal umbrella for consumers in Indonesia, has clearly regulated the obligation of business actors to include a label as proof of halal. The formulation of the problem in this study is about consumer protection efforts related to imported products without halal labels and Indonesian language labels according to the Consumer Protection Act. The research used is a normative juridical approach. The discussion materials used consist of primary legal materials and secondary legal materials. Furthermore, the analysis is carried out using the deduction method. Liability against importers can be requested civilly, criminally, and administratively. Based on the conclusion, it is recommended to provide legal certainty for consumers in Indonesia above, it is hoped that the government can increase supervision on the circulation of imported products in Indonesia.